Analysis of the phase diagram and microstructural transitions in phospholipid microemulsion systems using high-resolution ultrasonic spectroscopy - Hickey, Sinead (Langmuir : the ACS journal of surfaces and colloids, 2006)
In the present work, high-resolution ultrasonic spectroscopy was applied to analyze a pseudoternary phase diagram for mixtures consisting of water/isopropyl myristate/Epikuron 200 and a cosurfactant (n-propanol). Changes in the ultrasonic velocity and attenuation in the megahertz frequency range were measured in the course of titration of the oil/surfactant/cosurfactant mixture with water at 25 degrees C. The ultrasonic titration profiles showed several phase transitions in the samples, which allowed the construction of an "ultrasonic" phase diagram. Quantitative analysis of the ultrasonic parameters enabled the characterization of various phases (swollen micelles, microemulsion, coarse emulsion, and pseudo-bicontinuous) as well as the evaluation of the state of the water and the particle size. The particle size obtained for the microemulsion region ranged from 5 to 14 nm over the measured concentrations of water/isopropyl myristate/Epikuron 200 and n-propanol, which agreed well with the previous literature data